Rheumatoid Arthritis - Toumi, Hechmi (IntechOpen, 2022)
Rheumatoid arthritis (RA) is a chronic autoimmune disease generating joint pain and damage in which inflammation plays a major role. RA joints are inflamed and stiff. Symptoms include joint swelling and warmth causing fatigue affecting life's health-related quality. Still, there are many other medical conditions that can also be associated with your symptoms and signs. This book is not a substitute for a diagnosis from a healthcare provider. Yet, understanding your symptoms and signs and educating yourself about health conditions is important and can contribute to having the healthiest possible life. Herein, Professor Hechmi Toumi offers an edited volume with detailed new information on RA pathogenesis and explains both approaches and treatment options: recent clinical research and traditional methods.